UJI PERUNUT PADA REAKTOR PLUG-FLOW MENGGUNAKAN AIR BERSIH DENGAN VARIASI FISIK - Santoso, Rangga
Chemical reactor is very important in water treatment and wastewater treatment process. One of the chemical reactor type is a plug flow reactor. In a plug flow reactor, ideal flow conditions are required to achieve optimal treatment. Tracer test is a method to get ideal flow condition. This study was conducted to determine the ideal conditions for a plug flow reactor in a manner simulating to a small-scale reactor. Tracer substace used was a mixture of textile dyes containing Rhodamine B compound. Rhodamine B is used because of these compounds do not interfere with the flow and do not react with the particles in the water. Tracer substance was injected into the reactor with the pulse method, injected simultaneously in whole by 25 ml with a concentration of 1 g/L and on a discharge rate 0.0263 L/second and 0.0277 L/second in preliminary study . In one variation, obtained theoretical detention time of 350 seconds and experimental detention time of 82.78 seconds. In the second running, obtained theoretical detention time of 288 seconds and a detention time of 90.59 seconds experiment. In the main research, conducted several discharge variation and also physical condition modification such as additional baffle and rock. Discharge used are 0.0095 L/s and 0.02 L/s. Obtained theoretical detention time for discharge 1 is 463 second and 340 second for discharge 2. After experiment, obtained experimental detention time for unmodified reactor is 292 second for discharge 1 and 117 second for discharge 2. For reactor with additional baffle obtained experimental detention time is 300 second for discharge 1 and 162 second for discharge 2. Lastly for rock physical modification obtained experimental detention time is 186 second for discharge 1 and 145 second for discharge 2. Furthermore, obtained effective volume percentage for every variation. For unmodified reactor the effective volume percentage is 63.07% for discharge 1 and 34.41% for discharge 2. For baffle-modified reactor, the effective volume percentage is 64.79% for discharge 1 and 47.65% for discharge 2. Lastly for rock-modified reactor the effective volume percentage is 40.17% for discharge 1 and 42.65% for discharge 2. From the experimental detention time and effective volume percentage, it can be concluded that additional baffle is the best modification that can be used on plug flow reactor